Design of a Photoactive Bimetallic Cu‐Au@g‐C3N4 Catalyst for Visible Light Driven Hydroxylation of the Benzene Reaction through C–H Activation. Issue 34 (26th August 2018) - Bhuyan, Bishal; Devi, Meghali; Bora, Debashree; Dhar, Siddhartha Sankar; Newar, Rajashree
Abstract : In the present study, a new photoactive bimetallic Cu‐Au@g‐C3 N4 catalytic system was designed by impregnating Cu and Au NPs over the graphitic carbon nitrite (g‐C3 N4 ) surface. Characterization of the catalyst using multiple techniques illustrated that very small‐sized Cu and Au NPs were monodispersed on the g‐C3 N4 surface, which were obtained by the in situ reduction of the metal salts using sodium borohydride. The as‐synthesized bimetallic Cu‐Au@g‐C3 N4 catalyst efficiently catalyzed the hydroxylation of benzene (HOB) via C–H activation under visible light irradiation at room temperature. The dominant role of the synergistic interaction between Cu and Au NPs were further elucidated by high resolution transmission electron microscopy (HR‐TEM) studies and X‐ray photoelectron spectroscopy (XPS) analysis. This study may provide a new avenue for the preparation of photoactive bimetallic catalysts and offers insight into the synergistic interaction of bimetallic catalytic HOB reactions. Abstract : Visible light mediated hydroxylation of benzene via C–H activation with a novel bimetallic Cu‐Au@g‐C3 N4 photocatalyst.